2005
DOI: 10.1063/1.2140071
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature crystallized pyrochlore bismuth zinc niobate thin films by excimer laser annealing

Abstract: Articles you may be interested inStructure, composition and microwave dielectric properties of bismuth zinc niobate pyrochlore thin films Microwave dielectric and Raman scattering studies on bismuth zinc niobate thin films J. Appl. Phys. Laser deposition and dielectric properties of cubic pyrochlore bismuth zinc niobate thin films Influence of strain on the dielectric relaxation of pyrochlore bismuth zinc niobate thin films Appl. Phys. Lett. 84, 957 (2004); 10.1063/1.1646216Bismuth zinc niobate pyrochlore diel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…These characteristics were not significantly affected by substrate materials. The dielectric constant obtained here is the highest ever reported for thin BZN films processed at low‐temperature of <200°C or without heat treatment 1,5–12 . This high dielectric constant in the AD‐BZN films was attributed to the nanosized crystallines formed in the films.…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…These characteristics were not significantly affected by substrate materials. The dielectric constant obtained here is the highest ever reported for thin BZN films processed at low‐temperature of <200°C or without heat treatment 1,5–12 . This high dielectric constant in the AD‐BZN films was attributed to the nanosized crystallines formed in the films.…”
Section: Resultsmentioning
confidence: 46%
“…Recently, Park and colleagues 1,3–8 and several research groups 9–12 reported the fabrication and characterizations of bismuth–zinc (magnesium)–niobate, pyrochlore phase‐based thin films for embedded capacitor applications. The films showed good dielectric and leakage current performance even when they were fabricated at low‐temperature.…”
Section: Introductionmentioning
confidence: 99%
“…But, their dielectric constants are small. Bismuth‐based pyrochlores have relatively large dielectric constant and very low loss tangent . They have been widely studied for film capacitors, high frequency and microwave dielectric applications .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, paraelectric bismuth–zinc (magnesium)–niobate (BZN)–based thin films have attracted interest for embedded capacitor applications because they show a good dielectric constant (150–220) and leakage current performance even when fabricated at a low temperature 5–13 . Furthermore, BZN films show a large electric field dependence of their dielectric permittivity 9–13 .…”
Section: Introductionmentioning
confidence: 99%